Magical mermaids! based on the teleplay "Mermaid Mayhem" by Brian Swenlin and Jennifer Bardekoff - Aikins, Dave; Aikins, Dave; Bardekoff, Jennifer; Swenlin, Brian; Penguin Random House; Random House Children's Books; Viacom International (New York Random House, 2017)
"Shimmer and Shine visit a mermaid kingdom. Can they fix their mistakes?"--Page [4] of cover
At head of title: Nickelodeon Shimmer and Shine
English Stories
Keywords: Mermaids -- Juvenile fiction; Picture books; Readers; Mermaids; Mermaids -- Juvenile fiction; Early Reader; Readers (Primary)